Identifying traits and molecular markers for improvement of ear fertility in wheat - Boonsrangsom, Thanita (2016)
Wheat (Triticum aestivum L.) grain yield potential is generally sink-limited under favourable conditions with grain growth limited mainly by the number of grains formed per unit area. In the CIMMYT program in NW Mexico, novel large-ear phenotype traits (e.g. high assimilate partitioning to ear, high fertile florets ear-1) have been developed and may offer scope for increasing grain number per unit area (Gaju et al., 2009). In this study, ear fertility traits and their genetic regulation were investigated in backcross lines derived from novel large-ear doubled-haploid lines (UK Rialto x novel large-ear CIMMYT L14 line cross) backcrossed into either UK spring wheat Ashby or UK winter wheat Humber. Forty four BC3 near isogenic lines (NILs) (7 spring and 37 winter wheat NILs, currently BC3S5 and BC3S6) and 34 BC1S7 lines (18 spring and 16 winter wheat NILs, currently BC1S7) and their recurrent parents (Ashby or Humber, respectively) were chosen for physiological analysis in field experiments at University of Nottingham, UK and KWS, Thriplow, Hertfordshire, UK for evaluating novel variation for ear fertility traits and grain yield and specific introgressed target QTL on ear fertility traits and grain yield in 2012/13 and 2013/14. In highest/lowest performing BC3 spring NILs, above ground dry matter (AGDM) per main shoot increased by 97%, grain dry weight (GDW) ear-1 by 95% and grain number (GN) ear-1 by 68%, but grain yield was decreased by 71% associated with fewer ears m-2 (-87%) compared to the Ashby recurrent parent. For BC3 winter NILs, results showed that there was variation above Humber, for grain yield 100% DM (+22%), grains m-2 (+16%), harvest index (HI) (+6%), spikelets ear-1 (+14%), fertile spikelets ear-1 (+15%), rachis length (cm) (+24%) and thousand grain weight (TGW) (g) (+21%) (P<0.10). In the experiment at KWS Thriplow, the effects of the Tin1A gene in pairs of BC1S7 NILs contrasting in tiller number were investigated in the Ashby and Humber backgrounds. Amongst five pairs of spring NILs contrasting for the tiller inhibition Tin1A locus, the Tin1A lines were reduced in tillers m-2 (-16%), grain yield (-9%) and ears m-2 (-19%) but increased in spikelets ear-1 (+12%). In two pairs of winter NILs contrasting for the Tin1A locus, the Tin1A lines reduced tillers m-2 (-18%), grain yield (-6%), ears m-2 (-16%) but increased GN ear-1 (+20%), spikelets ear-1 (+11%) and GN spikelets-1 (+6%). The extent of tiller reduction was overall too severe in the spring NILs with Ashby background to lead to increased yield in the lines carrying the L14 allele. In winter NILs, grain yield and biomass were increased with high canopy green area and better maintenance of green area during grain filling. This suggested grain growth may have been partly limited by source supply of assimilate during grain filling possibly during the latter stages of grain filling. A strong relationship between individual grain weight and rate of grain filling was consistent in BC3 spring NILs. Grain weight was increased in BC3 winter NILs with increasing rate of grain filling but duration of grain filling was decreased. DNA samples from each BC3S5 line were screened using 8 SSR markers for the introgressed ear fertility QTLs identified in the Rialto x CIMMYT L14 DH population. The genotyping results showed the CIMMYT L14 allele for a novel QTL on chromosome 3A was associated with increases in ear fertility traits (grain number ear-1, spikelets ear-1, and grain DM shoot-1) amongst the BC3S5-6 lines when compared to the Humber recurrent parent and confirmed the presence of Tin1A gene in the Ashby background determining ear fertility and grain yield effects.